Enhancing actuarial education digital innovation via MindAppz eBook - Awang Chek, Mohd Zaki; Ismail, Isma Liana (2025)
The advancement of digital education has significantly improved higher education delivery, particularly in technical fields like actuarial mathematics. This study investigates the effectiveness of the MindAppz eBook, Introduction to Actuarial Mathematics, in enhancing students' comprehension, retention, and engagement. Employing a mixed-methods approach—including surveys, interviews, and performance comparisons—the study found that students who used the eBook performed 12% better in post-tests and demonstrated improved understanding in key actuarial topics such as annuities, premiums, and reserves. While the digital format encouraged independent learning and increased engagement, some students experienced digital fatigue and preferred hybrid approaches. These findings support the integration of blended learning models in actuarial education and highlight the importance of interactive and adaptive digital resources for future curriculum design.